Electrochemotherapy – Emerging applications technical advances, new indications, combined approaches, and multi-institutional collaboration. Issue 2 (February 2019) - Campana, Luca G.; Edhemovic, Ibrahim; Soden, Declan; Perrone, Anna M.; Scarpa, Marco; Campanacci, Laura; Cemazar, Maja; Valpione, Sara; Miklavčič, Damijan; Mocellin, Simone; Sieni, Elisabetta; Sersa, Gregor
Abstract: The treatment of tumors with electrochemotherapy (ECT) has surged over the past decade. Thanks to the transient cell membrane permeabilization induced by the short electric pulses used by ECT, cancer cells are exposed to otherwise poorly permeant chemotherapy agents, with consequent increased cytotoxicity. The codification of the procedure in 2006 led to a broad diffusion of the procedure, mainly in Europe, and since then, the progressive clinical experience, together with the emerging technologies, have extended the range of its application. Herein, we review the key advances in the ECT field since the European Standard Operating Procedures on ECT (ESOPE) 2006 guidelines and discuss the emerging clinical data on the new ECT indications. First, technical developments have improved ECT equipment, with custom electrode probes and dedicated tools supporting individual treatment planning in anatomically challenging tumors. Second, the feasibility and short-term efficacy of ECT has been established in deep-seated tumors, including bone metastases, liver malignancies, and pancreatic and prostate cancers ( long-needle variable electrode geometry ECT), and gastrointestinal tumors ( endoscopic ECT). Moreover, pioneering studies indicate lung and brain tumors as suitable future targets. A further advance relates to new combination strategies with immunotherapy, gene electro transfer (GET), calcium EP, and radiotherapy. Finally and fourth, cross-institutional collaborative groups have been established to refine procedural guidelines, promote clinical research, and explore new indications.